Occupational survey-based evidence of health status and welfare problems of workers with pneumoconiosis in China - Hu, Wenxiu; Wu, Wei-Ning; Qiao, Qingmei (Frontiers in Public Health, 2023)
Background Pneumoconiosis is the most dangerous occupational disease in China. According to unofficial records, nearly million migrant workers were affected by pneumoconiosis in 2011, with the number increasing annually. Among them, a large number of migrant workers suffering from pneumoconiosis were not medically diagnosed. Therefore, fundamental questions remain unanswered: what is the background of workers who receive a diagnosis of pneumoconiosis, and how does pneumoconiosis affect their future and well-being? Methods In this study, we identified and surveyed 1,134 workers with pneumoconiosis in seven selected regions in China with substantially high incidences of pneumoconiosis by using a combination of cluster sampling, convenience sampling, and snowball sampling. We used demographic, medical, and rehabilitation conditions and welfare questionnaires to collect the data. Results The findings highlighted the socioeconomic status of patients with pneumoconiosis. The majority of workers with pneumoconiosis were adult men who had received no higher education, who lived in rural households, and who were employed in mining or manufacturing industries. Among these workers, 52.8% had been exposed to dust at work for more than 10 years, and 53.1% received a diagnosis of stage II or III pneumoconiosis. More than half of the workers (569 workers, 50.2%) did not receive comprehensive, routine treatment; 33.4% (379 workers) visited a doctor when they experienced physical discomfort, and 6.6% (75 workers) never received treatment. Only 156 workers (13.8%) received rehabilitation services, whereas 978 workers (86.2%) never did. The study results also revealed the severe financial difficulties faced by patients with pneumoconiosis. Only 208 workers (18.3%) had access to work-related injury insurance, with the cost of pneumoconiosis treatment being a substantial burden for 668 workers (60.6%). Conclusion In this study, we explored the existing health and welfare problems faced by workers with pneumoconiosis in China and identified the social injustice and health disparities that these workers experience. We also clarified the primary challenges in implementing safety, health, and welfare policies for these workers and those who are exposed to high-risk environments, such as those working in mining.